Ekonomický rozvoj kanadské Arktidy a dopad těžby nerostných surovin na populaci Inuitů - Švecová, Marianna (Univerzita Karlova, Fakulta sociálních věd, 2017)
The bachelor thesis analyses and compares three main periods of the economic development in the Canadian Arctic, starting from the years 1950's until the end of the administrative of Prime Minister Harper in 2015. Mining of natural resources, as the base of the North's development, has been seen by the federal government also as a tool for cultural assimilation of Inuit into the dominant society. Nevertheless, participation of Inuit in mining activities and in fact in the whole employment culture has had serious impact on Aboriginal communities who have never been consulted about the federal strategy. However, while the first phase of development is characterized by strict colonialist approach of the government, the situation started to change during the second phase, characterized by a rising of Inuit's political participation and their first demonstrations of discontent. Although during the third, neoliberal era, several new mechanisms in order to improve the dialogue between Inuit, mining companies and the government were accepted, social conditions in Inuit communities remain below the Canadian average and with the government "laissez-faire" attitude they are not to be changed any time soon. Bakalárska práca sa zaoberá analýzou a porovnávaním troch hlavných období vo vývoji ťažby nerastných surovín v kanadskej Arktíde a jej dopadov na domorodých Inuitov, začínajúc 50. rokmi 20. storočia a končiac administratívou premiéra Harpera v rokoch 2006 až 2015. Ťažba nerastných surovín ako prostriedok, cez ktorý vláda podnikala svoju víziu ekonomického rozvoja oblasti zahájeného "Severnou víziou" premiéra Diefenbakera, sa stala tiež nástrojom na integráciu Inuitov do modernej kanadskej spoločnosti. Zapojenie do systému zamestnania v baniach však malo na populáciu Inuitov hlboké socio-ekonomické následky, ktoré sú v komunitách viditeľné dodnes. Kým však v počiatkoch ťažobných aktivít bol prístup vlády k integrácii pôvodných obyvateľov značne kolonialistický, v druhej sledovanej fáze sa postoj vďaka politickej ...